Glassy Cells adenocarcinoma of the uterine cervix in young patient with HPV: case report - Martins, Thais Rodrigues Silva; Araújo, Leandro F.; Marangon, Luna M.; Carvalho, Vinicius J.C.; Sampaio, Rodrigo S.; Monnerat, Andrea L.C.; Ramos, Rosana G.; Bravo, Renato S.; Passos, Mauro Romero L. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: cervical cancer is the second most common cancer in women worldwide and the third among the female population in Brazil. HPV plays an important role in the development of cervical cancer, being present in 95% of cases of cancer of the cervix. Glassy cells carcinoma is a poorly differentiated mixed adenosquamous carcinoma, rare, aggressive and highly resistant to radiotherapy. It typically affects young women, with peak incidence between the third and fourth decades of life. It is associated with types 16 and 18 of HPV and its evolution is acelerated during pregnancy. The average survival time after diagnosis is 10 months. Case Report: woman, 26 years old, multiparous, with a history of condyloma acuminata, genital lesions that had increased in their last pregnancy, having evolved with exophytic masses diagnosed as glassy cell carcinoma, and aggressive course with early metastases not responsive to radiation therapy and progression to death in 16 months. Conclusion: glassy cells carcinoma is distinguished by aggressiveness and speed of its development, leading child-bearing age and productive young women to death. In view of its low response to anticancer therapies, we highlight the importance of its prevention, early diagnosis and treatment, possible through the use of condoms, the vaccine against HPV and cervical cytology at regular collection of endocervical material and effective monitoring.